Optimization of pole characteristic in pole vaulting using three-dimensional vaulter model - Ohshima, S.; Nashida, Y.; Ohtsuki, A. (Procedia Engineering, 2010)
Pole vaulting has progressed rapidly in terms of mechanical properties and appearance as a result of the use of a flexible fiberglass pole. Various researchers have modeled the vaulter body as a series of rigid-links, limited to a two-dimensional plane. In this research, a combination system consisting of a flexible pole and three-dimensional vaulter model which consists of a rigid-body link with a twist motion is presented. Here, the simulation analysis optimizes the pole characteristics and the joint torque with the application of a Genetic Algorithm. The control parameters were the joint torque and pole stiffness. From the results, it was clarified that there is optimal pole characteristic which is linked to the vaulter's initial velocity.